Efectiveness of Ocimum sanctum Linn. Leaves Ethanol Extract on Mortality Raillietina echinobothrida In Vitro - Jessica Giovani; Setiawan Koesdarto; Mirny Lamid; Sri Agus Sudjarwo; Suryo Kuncorojakti (Journal of Parasite Science (JoPS), 2018)
The aims of the research are to prove the anthelmintic effects of Ocimum sanctum Linn. leaves ethanol extract on Raillietina echinobothrida in vitro and to know the value of LC50 and LC90of Ocimum sanctum Linn. leaves ethanol extract. The research used completely randomized design. The research had five treatments and each treatment was done in four replications. The research used 5 Raillietina echinobothrida adult worms for each treatment and all replications. The observation and the recording were done at the first hour until the sixth hour of the research. The Raillietina echinobothrida adult worms were noted dead if there was no movement when they were disturbed by anatomic tweezer, the death of Raillietina echinobothrida were confirmed when they dipped mildly in warm water (50Â°C) and they showed no movements. The acquired data was analyzed using ANOVA and continued with LSD (5%). The results were Ocimum santum Linn. ethanol extract has the anthelmintic activity in 1.25%, 2.5%, 5% and 10% concentrations. The LC50 and LC90 was analyzed using probit analysis. The results of LC50 calculation were 7.8% at the third hour, 6% at the forth hour, 3.2% at the fifth hour, 2.5% at the sixth hour and the results of LC90 were 6.5% at the fifth hour, 5.2% at the sixth hour. The higher concentration of the extract, the higher anthelmintic activity worked.